Vanadium and biomarkers of inflammation and oxidative stress in diabetes: A systematic review of animal studies - Faezeh Ghalichi; Alireza Ostadrahimi; Maryam Saghafi-Asl (Tabriz University of Medical Sciences, 2022)
Background: Oxidative stress has a significant role in the commencement and development of hyperglycemia. Vanadium, as a transitional metal with redox properties, enters the redox process, produces free radicals, and distracts the pro-antioxidant balance. The present animal systematic review aimed to assess the effect of vanadium supplementation on inflammation and oxidative stress biomarkers in diabetes-induced animals. Methods: A systematic search was conducted using the PubMed, Scopus, and web of science databases from 1990 to 2021, according to the inclusion and exclusion criteria. The search strategy was based on the guidelines for systematic review of animal experiments and Preferred Reporting Items for Systematic Reviews (PRISMA). Criteria for eligibility were animal-based studies, evaluating the therapeutic effects of vanadium on inflammatory and oxidative stress biomarkers in diabetes. The Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) tool was used for assessing the methodological quality of included studies. Results: In the present study, 341 articles were evaluated out of which 42 studies were eligible for inclusion. The majority of the studies confirmed the advantageous properties of vanadium on inflammatory and oxidative stress biomarkers. A minor risk of bias was reported, based on the SYRCLE's tool. Conclusion: According to the findings, well-designed clinical trials are warranted to assess the long-lasting effects of various vanadium compounds on inflammatory and oxidative stress biomarkers.